2016
DOI: 10.5294/laclil.2016.9.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Analysing a whole CLIL school: Students’ attitudes, motivation, and receptive vocabulary outcomes.

Abstract: CLIL keeps on gaining ground in the European educational context, one clear example is Spain, where the number of schools adopting this methodology has kept growing exponentially in recent years. The present study has a dual perspective looking at the motivation of students towards English and CLIL and showing students' receptive vocabulary outcomes. All students (n=403) enrolled in secondary education in a bilingual school fulfilled a questionnaire and completed two receptive vocabulary level tests (VLT 2k an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Much of the research on receptive outcomes of CBI has focused on receptive vocabulary. Six studies reported mixed findings on CBI's effectiveness for developing receptive vocabulary with three finding significant differences in favor of CBI (Canga-Alonso, 2015a, 2015bXanthou, 2011) and three finding no significant differences between CBI and non-CBI groups (Agustín-Llach, 2017; Arribas, 2016;Gierlinger & Wagner, 2016). The three studies showing positive effects of CBI on receptive vocabulary all took place with primary school students, whereas those showing no difference studied both secondary (N=2) and primary (N=1) schools.…”
Section: Receptive Language Skillsmentioning
confidence: 99%
“…Much of the research on receptive outcomes of CBI has focused on receptive vocabulary. Six studies reported mixed findings on CBI's effectiveness for developing receptive vocabulary with three finding significant differences in favor of CBI (Canga-Alonso, 2015a, 2015bXanthou, 2011) and three finding no significant differences between CBI and non-CBI groups (Agustín-Llach, 2017; Arribas, 2016;Gierlinger & Wagner, 2016). The three studies showing positive effects of CBI on receptive vocabulary all took place with primary school students, whereas those showing no difference studied both secondary (N=2) and primary (N=1) schools.…”
Section: Receptive Language Skillsmentioning
confidence: 99%
“…More recently, Arribas (2016) has examined a whole CLIL school analysing students' attitudes, motivation and receptive vocabulary outcomes. The results showed that CLIL learners scored higher in receptive vocabulary tests due to their greater motivation.…”
Section: Research On Motivationmentioning
confidence: 99%
“…The results reported that the CLIL students outperformed the control group in the tests, and their attitudes towards learning vocabulary being exposed to CLIL were positive. Similar to this study, Arribas (2016) attempted to discover the outcomes of the students' receptive vocabulary aside from their motivation towards learning English. The results showed that the CLIL group scored higher in receptive vocabulary tests due to their higher motivation.…”
Section: Introductionmentioning
confidence: 99%